Adsorption of Congo Red Dye from Aqueous Solutions using Neem Leaves as Adsorbent - Pratap Raghuvanshi, Shiv; Singh, Renu; Kaushik, C.P. (Asian Journal of Chemistry, 2010)
A low cost absorbent prepared from neem leaves for the removal of congo red dye from aqueous solution has been studied. Experiments in batch reactor were carried out to study the removal efficiency of neem leaves towards the adsorption of congo red dye (adsorbate) by stirring it with neem leaves powder (adsorbent). Kinetics study of adsorption and equilibrium studies were carried out by varying different parameters like size of the adsorbent particles, initial concentration of dye and the adsorbent dosage. An adsorption rate model has been developed. The experimental data have also been studied in light of Langmuir and Fruendlich. Adsorption equilibrium data fit most satisfactorily to Langmuir adsorption isotherm.